Effect of molecular hydrogen, a novelly-established antioxidant, on the retinal degeneration of hereditary retinitis pigmentosa: an in-vivo study - Yan, Weiming; He, Qiurui; Long, Pan; Chen, Tao; Zhang, Lei; Wang, Haiyan (Frontiers in Pharmacology, 2024)
Objective Our research was performed in order to explore the effects of molecular hydrogen (H 2 ), a novelly-established antioxidant, on the retinal degeneration in rd1 mice, an animal model of inherited retinitis pigmentosa (RP). Methods The rd1 mice were divided randomly into control and H 2 intervention groups. Mice from other groups received H 2 intervention in three modes, two modes of the hydrogen gas (HG) and one model of hydrogen-rich saline (HRS). At 14 days post born (P14) and P21, various indicators were detected in all mice, including ERG, fundus photography and OCT examination. Results The ERG amplitude in mice from the control and H 2 intervention groups showed no statistical differences (P > 0.05). At P14 and P21, no significant difference in the distance from the retinal pigment epithelium to the outer plexiform layer on OCT from mice of the above two groups was found (P > 0.05).The thickness of the outer nuclear layer (ONL) in mice at P14 and P21 showed no statistical differences between the control group and the H 2 intervention group (P > 0.05). In the aspect of the number of Iba1-positive cells, we did not found any significant differences between the two groups (P > 0.05). Conclusion Different forms of H 2 intervention (hydrogen-rich saline and hydrogen gas) had no obvious effects on the course of retinal degeneration in rd1 mice. The specific mechanism of photoreceptor degeneration in the hereditary RP mouse model may be different, requiring different medical interventions.